2010
DOI: 10.1029/2010gl043811
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave dispersion across Tibet: Direct evidence for radial anisotropy in the crust

Abstract: International audienceRecordings in western Tibet of Rayleigh and Love waves at periods less than 70 s from aftershocks of the 2008 Sichuan earthquake cannot be matched by an isotropic velocity model beneath Tibet. These intermediate‐period Rayleigh and Love waves require marked radial anisotropy in the middle crust of Tibet, with the vertically polarized S‐waves propagating more slowly than S‐waves with horizontal polarization. The magnitude of anisotropy inferred using paths entirely within Tibet is slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…Subsequently, Duret et al . [] presented evidence from individual seismograms using aftershocks of the Wenchuan earthquake of 12 May 2008 that the Rayleigh‐Love discrepancy is so significant for paths crossing Tibet that crustal radial anisotropy probably also extends into eastern Tibet. Huang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Duret et al . [] presented evidence from individual seismograms using aftershocks of the Wenchuan earthquake of 12 May 2008 that the Rayleigh‐Love discrepancy is so significant for paths crossing Tibet that crustal radial anisotropy probably also extends into eastern Tibet. Huang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Strong azimuthal anisotropy in the upper crust is observed in South Africa and has been related to extension at the southern tip of the African Rift (Adam and Lebedev, 2012). Midcrustal strong radial anisotropy has been observed in Tibet (Duret et al, 2010;Shapiro et al, 2004), whereas radial anisotropy has been inferred in the lower crust in the Aegean Sea (Endrun et al, 2008(Endrun et al, , 2011 and azimuthal anisotropy in the lower crust of the western United States (Lin et al, 2011).…”
Section: Crustal Anisotropymentioning
confidence: 94%
“…Larger values of x $ 1.18 (Debayle and Kennett, 2000;Maupin and Cara, 1992) are challenging to reconcile with olivine LPO and may require additional fine-horizontal layering. Large Rayleigh-Love discrepancies, with fast Love waves, are not limited to waves sensitive to the uppermost mantle, but have also been found at periods sensitive to the crust in tectonic regions, such as Tibet (Duret et al, 2010) and the Aegean Sea (Endrun et al, 2008).…”
Section: Surface Waves and Upper Mantlementioning
confidence: 98%
“…Clark et al () suggested the presence of crustal flow in the NE Tibetan plateau via fitting the observed northeastward sloping topography by inducing an underlying lower crustal channel with a thickness of 15 km. Recent geophysical observations offer several lines of evidence, such as low velocity zone (Bao et al, ; Schoenbohm et al, ; Yang et al, ) and strong radial anisotropy (Duret et al, ; Li et al, ; Shapiro et al, ; Xie et al, ) in the middle and/or lower crust, in support of the existence of crustal flow in this region. However, the low and moderate Poisson's ratio (Wang et al, ; Xu et al, ) indicated a generally felsic crust in this region, which is contradictory to the mafic crustal composition predicted by the lower crustal flow model (Pan & Niu, ).…”
Section: Introductionmentioning
confidence: 95%